UJI DAYA TERIMA DAN NILAI GIZI DONAT YANG DIMODIFIKASI DENGAN TEPUNG BIJI NANGKA DAN TEPUNG BAYAM - Rahmi Sartika Daulay; Etti Sudaryati; Evawany Y Aritonang (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Food diversification efforts can be done by using local food. Jackfruit seeds and spinach are one of the local food with high nutrients. Jackfruit seeds and spinach processed into flour  an effort to become snack food utilization. This study is an experimental study. Donuts jackfruit seeds and spinach consists of three factors, wheat flour, jackfruit seeds flour, and spinach flour with 2 treatments. Each first treatment with symbols A1 uses a combination of jackfruit seeds flour,  spinach flour, and wheat flour as much as 10% : 6% : 84%, and the second treatment with symbols A2 uses a combination of jackfruit seeds flour,  spinach flour, and wheat flour as much as 6% : 10% : 84%. Panelists in this study are 30 students of SMPN 1 Padangsidimpuan. The results showed that the organoleptic test results donuts jackfruit seeds and spinach most preferred based taste, aroma, colour, and texture are donuts jackfruit seeds and spinach A1 with the category like. Based on analysis of the nutrient content of protein, iron, and calcium donuts jackfruit seeds and spinach which has the highest protein content is donuts A2 much as 10.1% per 100 gram, while the donuts jackfruit seeds and spinach which has the highest iron content is donuts A2 as much as 2.76 mg per 100 gram, and donuts jackfruit seeds and spinach which has the highest calcium content donuts A1 as much as 120.3 mg per 100 gram. It is advisable in order to carry out further research on donuts jackfruit seeds and spinach to improve the nutritional content and dissemination of information need to be made and received donuts from jackfruit seeds flour and spinach flour is used as a snack food for school children. As well as the need to do further research to see the content of nutrients contained in donuts jackfruit seeds and spinach. Keyword: Jackfruit seeds flour, Spinach flour, Donuts, Acceptability, Nutrient content